Gräsrotsmuseer: Vem bryr sig om museerna — fågel, fisk eller gräsrötter mitt emellan? Reflexioner från några museiresor - Björkroth, Maria (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
Community museums are a rising number of the museums around the world. This article based on a period of guest lecturing in Cape Town, South Africa discusses the work of creating new community museums from below. The article mentions the following museums: Lwandle Migrant Labour Museum, The District Six Museum, The South African Jewish Museum and The Boo-Kap Museum. The museum consists of activities and processes that engage people. If the museum fails to engage sustainable elaboration it dies. A museum that is ready and done, relatively quickly loses its relevance for the developing society. The growth of small and medium size community museums are an important signal to the museum society and governmental foundations to rethink their priorities.